Answer:
[tex]y=\frac{1}{2}x+1[/tex] is in the slope-intercept form.
so the slope will be:
and y-intercept will be:
Step-by-step explanation:
Given the equation
[tex]x-4=2(y - 3)[/tex]
As we know that [tex]y = mx+b[/tex] is the slope-intercept form of a line where [tex]m[/tex] is the slope and [tex]b[/tex] is the y-intercept.
Converting to slope-intercept form
[tex]x-4=2(y - 3)[/tex]
switching sides
[tex]2\left(y-3\right)=x-4[/tex]
[tex]2y-6=x-4[/tex]
[tex]2y=x-4+6[/tex]
[tex]2y=x+2[/tex]
[tex]y=\frac{1}{2}x+1[/tex]
As [tex]y = mx+b[/tex] is the slope-intercept form of a line where [tex]m[/tex] is the slope and [tex]b[/tex] is the y-intercept.
Therefore, [tex]y=\frac{1}{2}x+1[/tex] is in the slope-intercept form.
so the slope will be:
and y-intercept will be: